Analysis of the Effect of the COVID-19 Pandemic on Stock Return of Banking Company - Desya Permatasari; Vidyarto Nugroho (International Journal of Application on Economics and Business, 2023)
This research examines the influence of COVID-19 on stock return in banking companies listed on the Indonesia Stock Exchange in 2020 between the 2nd of March and the 30th of December, 2020. To assess the effect of COVID-19, the growth of confirmed cases, the growth of death cases, the growth of recovery cases, and the new normal policy are used as independent variables, with stock returns as the dependent variable. Research method using quantitative. Sampling using probability sampling with census method. Testing data using the program EViews 12. The results reveal that, the growth in confirmed cases also the growth in death cases due to COVID-19 have a significant and negative effect on the stock returns of banking companies. The growth in COVID-19 recovery cases has a negative influence on the stock return, while the new normal policy has a positive influence on stock return of banking companies.